1981
DOI: 10.1002/em.2860030311
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of the mycotoxin botryodiplodin in the salmonella typhimurium/microsomal activation test

Abstract: Botryodiplodin, a mycotoxin synthesized by some strains of Penicillium roqueforti was tested for lethal and mutagenic effects on Salmonella typhimurium (TA98). Botryodiplodin was active in the histidine reversion system without metabolic activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…In addition, (±)-botryodiplodin induced phytotoxic responses indistinguishable from those induced by (−)-botryodiplodin, when compared in duckweed (L. pausicostata) plantlet cultures and soybean leaf discs in culture (see below). Identical activity of (±)-botryodiplodin and (−)-botryodiplodin is consistent with extensive studies on the mechanism of action of (−)-botryodiplodin by Moule et al (1981a;1981b; [36][37][38], which indicated that the toxin acts by chemical reactions in cell nuclei that covalently cross-link proteins to DNA, and not by interacting with a chiral binding site on any enzyme or receptor that might require an optically active form. Although (+)-botryodiplodin has been prepared by chemical synthesis [39], its biological activity, or the lack thereof, has not been reported by these investigators or others.…”
Section: Synthesis Of (±)-Botryodiplodinsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, (±)-botryodiplodin induced phytotoxic responses indistinguishable from those induced by (−)-botryodiplodin, when compared in duckweed (L. pausicostata) plantlet cultures and soybean leaf discs in culture (see below). Identical activity of (±)-botryodiplodin and (−)-botryodiplodin is consistent with extensive studies on the mechanism of action of (−)-botryodiplodin by Moule et al (1981a;1981b; [36][37][38], which indicated that the toxin acts by chemical reactions in cell nuclei that covalently cross-link proteins to DNA, and not by interacting with a chiral binding site on any enzyme or receptor that might require an optically active form. Although (+)-botryodiplodin has been prepared by chemical synthesis [39], its biological activity, or the lack thereof, has not been reported by these investigators or others.…”
Section: Synthesis Of (±)-Botryodiplodinsupporting
confidence: 86%
“…(±)-Botryodiplodin was selected for use in these studies, because it is readily synthesized chemically in larger amounts than were available by fermentation [32]. The mechanism of action of botryodiplodin has been extensively studied by Moule et al [36][37][38], who provided evidence for non-enzymatic (i.e., chemical) crosslinking of DNA to protein. There have been no reports of botryodiplodin binding specifically to a chiral binding site on any enzyme or receptor.…”
Section: Preparation Of (±)-Botryodiplodinmentioning
confidence: 99%
See 1 more Smart Citation
“…botryodiplodin (BD) (6, 63, 96), a mutagenic mycotoxin (67). BD forms DPCs in eukaryotic cells (66,69) and blocks DNA synthesis in a manner consistent with a DNA-damaging agent (68).…”
Section: Lge 2 Cross-links Dna With Proteinsmentioning
confidence: 99%
“…Penicillium stipitatum Thom] [ 29 ], M. phaseolina [ 21 ] and others [ 30 ]. This mycotoxin has received attention due to its potent antibiotic [ 31 ], anticancer [ 32 ] mutagenic, cytotoxic [ 33 ] and phytotoxic activities [ 34 ], as well as the ability to induce protein-DNA crosslinking in mammalian cells [ 35 , 36 ]. Among (−)-botryodiplodin producing fungi, P. roqueforti is a common contaminant of processed food [ 28 ].…”
Section: Introductionmentioning
confidence: 99%